ĮŽYMUSIS MINTIES SFEROS PRATURTINIMAS - Plečkaitis, Romanas (Problemos, 2005)
Tiriama filosofijos klasiko apibrėžtis ir jo kūrybos didumo kriterijai. Šiuo aspektu žvelgiama į I. Kanto kûrybos sukeltas inovacijas ir jos šiuolaikinį aktualumą.Reikšminiai žodžiai: filosofijos klasikas, didumo filosofijoje kriterijai, antlaikiškumas, įpėdinystė.THE GRAND ENRICHMENT OF THE MIND SPHERERomanas PlečkaitisSummary The article reflects on the question of the greatness in philosophy and Immanuel Kant’s contribution as the grand enrichment. The academic world of the professors of philosophy is the instance that defines the criterion of greatness in philosophy. Both the work’s style and mistakes are not considered as such criterion. Kant was one of the creators of the eighteen-century mind. He discovered the new Foundations for person and value of human beings. Keywords: classic of philosophy, criterion of majesty in philosophy.